Bibliometrics: Analysis of the Development of Desalination Membranes in the Past Decade to 2022 - Triadi, Hari Agung (Jurnal Nusantara Mengabdi, 2025)
Purpose: This study uses a bibliometric method to computational mapping analysis with VOSviewer to look at how chemical particle desalination membrane research has evolved. Methodology: By using the publish or perish reference manager tool, the Google Scholar database was queried for the article data. By using the phrase "C`hemistry Particle Desalination Membrane" the search is directed by the title and abstract of the article. There were 1024 items that were thought to be pertinent. The research period considered for the study is the most recent ten years of Google Scholar-indexed articles (2012 to 2022). Results: The findings showed an upward trend in the number of papers on desalination membranes. In desalination membrane research, there are 5 clusters and 5 topics that are frequently discussed. These are Cluster 1: Treatment (number of links 52, total link strength 99, accurness 65), Cluster 2: Composite (number of links 34, total link strength 49, accurness 40), Cluster 3: Nanofiltration (number of links 42, total link strength 92, accurness 52), Cluster 4: Desalination performance (number of links 39, total link strength 93, (number of links 34, total link strength 75, accuracy 38). Conclusion: Bibliometric analysis shows rapid growth in membrane desalination research, focusing on treatment, membranes, and performance, with notable gaps and limited studies on “Chemistry Particle Desalination Membrane”. Limitations: The limitation of this research wass focused on the development of desalination membranes in the last 10 years using bibliometric analysis. Contribution: This study can provide an explanation that serves as a foundation for knowledge about the development of desalination membrane.